Pengaruh Batas Insisi, Indeks Mitosis, Dan Tumor Nekrosis Terhadap Angka Rekurensi Tumor Phyllodes - Lestari, Dian Yuliartha; Prihanti, Gita Sekar (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
Effect of Incision Boundary, Mitosis Index, and Tumor Necrosis on the Recurrence Rate of Phyllodes Tumors Background: Phyllodes tumor is one neoplasms fibroepitelial rare, approximately less than 1 % of all breast neoplasms. Determination of prognosis of phyllodes tumors based on histopathologic classification is difficult to implement. To evaluate the phyllodes tumor, an important marker for prognostic factors, mainly based on the criteria of phyllodes tumor itself (such as mitotic index, limits the incision). Objective: To determine the effect limits the incision, mitotic index and tumor necrosis against phyllodes tumor recurrence rate. Methods: An observational analytic study of the period 2009-2011 and followed through 2014. To determine the effect on recurrence rate limit incision Mann Whitney test , to determine the effect on the mitotic index recurrence rate testunpaired t -test , and to determine the effect of the tumor necrosis recurrence rate chi square test. Result: Obtained 16 samples that met the inclusion criteria with 10 samples and 6 samples did not relapse relapse. There were no influences between adjacent incisions (p = 0.05) , mitotic index (p = 0.06) , and tumor necrosis (p = 0.152) for phyllodes tumor recurrence rate Conclusion: There were no influences between adjacent incision, mitotic index , and tumor necrosis against phyllodes tumor recurrence rate